The Role of Temporary Use in Urban Regeneration: Ordinary and Extraordinary Approaches in Bristol and Liverpool. (20th October 2019) - Martin, Michael; Deas, Iain; Hincks, Stephen
ABSTRACT: This paper attempts to extend research on the temporary reuse of brownfield land through an examination of its role in regeneration strategies. The analysis draws upon empirical experience in two case study areas: one, Bristol's Temple Quarter where regeneration policy has tried purposely to promote temporary use, and the other, Liverpool's Creative Quarter, where policy has attempted retrospectively to capitalize upon 'meanwhile' development. Drawing on interviews with key regeneration and development actors, the paper demonstrates that regeneration strategies in different local economic contexts are poorly attuned to the needs of temporary users, who assume disproportionate levels of risk.